Evaluasi Tata Ruang Smart City Berbasis Persepsi Masyarakat di Kota Gorontalo - Irwan Wunarlan (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
The development of the Smart City concept in Indonesia not only emphasizes the use of information technology, but also on the quality of urban spatial planning that is able to support the comfort, sustainability, and quality of life of the community. This study aims to evaluate the spatial performance of Smart City in Gorontalo City based on the perception of the public as direct users of city space. The approach used is descriptive quantitative with data collection through a structured questionnaire with an assessment scale of 1–10. The research sample amounted to 150 respondents spread across nine sub-districts in Gorontalo City. The indicators analyzed include the availability of public spaces and public facilities, the availability of green open spaces, and the level of comfort and satisfaction of the community with urban spatial planning. The analysis method used is descriptive statistical analysis to obtain the average value of each indicator. The results of the study show that the spatial performance of Smart City in Gorontalo City is in the good category in all indicators. The availability of public spaces and public facilities obtained an average score of 8.37, the availability of green open space of 7.57, and the comfort and satisfaction of the community of 8.51. However, green open space is the lowest indicator of value, indicating that there is still a gap between sustainable spatial policies and realization on the ground. This study concludes that public perception is an important instrument in the evaluation of Smart City spatial planning and needs to be systematically integrated in urban spatial planning policies that are sustainable and oriented to the needs of residents.